Leaf Structural Traits Vary With Plant Size in Even-Aged Stands of Sapindus mukorossi - Chang, Yunni; Xu, Chaobin; Yang, Hong; Zhou, Junxin; Hua, Weiping; Zhang, Shihe; Zhong, Quanlin; Li, Baoyin (Frontiers in Plant Science, 2021)
Sapindus mukorossi Gaertn., an important oleaginous woody plant, has garnered increasing research attention owing to its potential as a source of renewable energy (biodiesel). Leaf structural traits are closely related to plant size and affect fruit yield and oil quality. However, plant size factors that predominantly contribute to leaf structural traits remain unknown. Therefore, the purpose of this study was to understand the associations between leaf structural traits and plant size factors in even-aged stands of Sapindus mukorossi. Results showed that leaf length (LL) and leaf area (LA) markedly increased with increasing diameter at breast height (DBH) and tree height (TH), although other leaf structural traits did not show noticeable changes. Difference in slopes also indicated that the degree of effect of plant size factors on leaf structural traits was in the order of TH>DBH. Leaf structural traits show no systematic variation with crown width (CW). LA was significantly positively correlated with LL, leaf width (LW), LL/LW and leaf thickness (LT), and was significantly but negatively correlated with leaf tissue density (LTD) and leaf dry mass content (LDMC). Specific leaf area (SLA) was significantly negative correlation with LT, LDMC and LTD. LTD show significantly positive correlation with LDMC, but negative correlation with LT. The results was critical to understand the variability of leaf structural traits with plant size, can provide theroretical foundation for further study in the relationship between leaf structural traits and fruit yield, and regulate leaf traits through artificial management measures to promote plant growth and fruit yield.